1968
DOI: 10.2136/sssaj1968.03615995003200040041x
|View full text |Cite
|
Sign up to set email alerts
|

Linear Extensibility as Calculated from Natural‐Clod Bulk Density Measurements

Abstract: Use of a coating that is flexible permits measurement of bulk density of natural clods at more than one moisture content. Linear extensibility, expressed as a coefficient (COLE) or as change in horizon thickness, can be calculated from the increase in bulk density between the water content at ⅓‐bar tension and oven dryness. Extensibility data are given for a Marias soil (Entic Chromoxerert). Composition of the Marias soil remains similar with depth but the structure changes. COLE values are affected by the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
7

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 0 publications
3
54
0
7
Order By: Relevance
“…The results indicated that profiles AH-05, AH-09, HN-03 and HN-10 showed high values of COLE in the sub-layers with high percentage of clay content and CEC. High COLE values are also found in other studies (Moustakas, 1990) and COLE value greater than 0.03 cm cm -1 suggests having a high amount of montmorillonite (Grossman et al, 1968). XRD analysis (Figs 3, 4) showed that all profiles of the soils of Northern China are composed of smectite (montmorillonite) and vermiculite, so we can say that the mineralogy of the soils was mainly responsible for the high values of COLE in our samples.…”
Section: Discussionsupporting
confidence: 84%
“…The results indicated that profiles AH-05, AH-09, HN-03 and HN-10 showed high values of COLE in the sub-layers with high percentage of clay content and CEC. High COLE values are also found in other studies (Moustakas, 1990) and COLE value greater than 0.03 cm cm -1 suggests having a high amount of montmorillonite (Grossman et al, 1968). XRD analysis (Figs 3, 4) showed that all profiles of the soils of Northern China are composed of smectite (montmorillonite) and vermiculite, so we can say that the mineralogy of the soils was mainly responsible for the high values of COLE in our samples.…”
Section: Discussionsupporting
confidence: 84%
“…La deformación del suelo se estimó por medio del coeficiente de extensibilidad lineal (COEL) que permite establecer la variación unidimensional del volumen de suelo desde que este se encuentra saturado hasta que se seca (Grossman et al, 1968). Para determinar la contracción del volumen de suelo como consecuencia del secado (COELh) se uso la siguiente ecuación:…”
Section: Coeficiente De Extensibilidad Linealunclassified
“…Para determinar la deformación del suelo producto de la compactación (COEL m ) durante el ensayo de consolidación se modificó la ecuación propuesta por Grossman et al (1968) …”
Section: Coeficiente De Extensibilidad Linealunclassified
“…Franzmeier and Ross (1968) and McCormack and Wilding (1975) found that total clay gave the best correlation with COLE, while Anderson et al (1973) found that fine clay gave the highest correlation to the properties they investigated. Ross (1978) COLE was calculated as (Dbd/Db)r/3-1 (Grossman et al 1968 (Eltantawy and Amold 1973). The specific surface area of soils was computed from the surface area of coarse and fine clay fractions.…”
mentioning
confidence: 99%